Rekayasa Prototype Kran Otomatis Berbasis Arduino Uno - Mohammad Taufan Asri Zaen; Yuliadi Yuliadi; Khairunnazri Khairunnazri; Chaerun Hadiyan Syah (Forum Kerjasama Pendidikan Tinggi, 2021)
The need for cleanliness and availability of water for the community is also getting higher. Currently, people use conventional faucets which can cause waste because the water faucets are not tightly closed or must be closed directly. Technological advancements need to be innovated to help the community in the movement to save clean water, one of which is the Arduino microcontroller. Based on these problems, the author made a prototype for making automatic water faucets equipped with motion detection sensors, ultrasonic sensors HC-SR04, servo motors as a driver to open the closing valve so that the faucet can release water and a relay to disconnect or connect the circuit that works automatically. With automatic faucets can make it easier for people to control the use of water. Arduino uno tool as controller and data processor.